Constraints to maternal healthcare access among pastoral communities in the Darussalam area of Mudug region, Somalia “a qualitative study” - Duale, Hodan A.; Farah, Abdiqani; Salad, Abdi; Gele, Sumaya; Gele, Abdi (Frontiers in Public Health, 2023)
Background. While countries embrace efforts to achieve Sustainable Development Goals (SDG) goal 3.1 (to reduce the global maternal mortality ratio to less than 70 per 100 000 live births by 2030 and end preventable deaths of new-borns and children), an estimated 2.5 million pastoralists in Somalia are struggling to access maternal and child healthcare services. Institutional delivery and access to antenatal care remained to be a challenge in Somalia, where pastoralism is a common means of livelihood. The aim of this study is to explore the maternal health services available for settled pastoralists (transhumant) and their families who still practise nomadic pastoralism in the Mudug region of Somalia.Methods. A qualitative study, including 14 interviews and one FGD, was conducted in Darussalam village (a transhumant village along the border between Somalia and Ethiopia), Puntland State, from December 2022 to January 2023. The study participants were community members who support the maternal and child health clinic (MCH), village administration, and health providers.Results. We found that the efficiency of the health facilities that serve for pastoralist women and children are hampered by staff-related, supply-related, patients-related and referral-related constraints. This study highlights that the absence of essential supplies, the unmet need for training among the staff as well as the absence of important facilities in the MCH such as ambulance and blood bags Conclusion. Numerous strides could be made in the provision of affordable maternal healthcare to pastoralist communities in Darussalam areas of the Mudug region when organizations that support health care in Somalia and the Ministry of Health include pastoralists' healthcare in their priorities.